Rural revitalization: Tapping into new opportunities - Steiner, Achim; Fan, Shenggen (International Food Policy Research Institute, 2019)
Rural revitalization is a way of positively transforming rural areas for present and future generations, as described in this signature chapter co-authored with UNDP. Rurbanomics is an approach to revitalization that frames rural economies as equal partners with urban economies, emphasizing the vitality of rural economies. Forging links between rural and urban economies, not only with megacities but also with smaller towns and cities, will play a major role in revitalization, particularly in improving employment opportunities to boost rural incomes and rural-urban market links that can provide both urban and rural populations with healthy diets. Rural revitalization will also require investments in the off-farm and nonfarm sectors, information and communication technologies, education, governance, rural health, and a healthy environment. These building blocks can create vibrant rural areas that can attract and retain employed, educated, and healthy rural residents.